Biologic Drugs Treatment of Chronic Urticaria - Javad Ghaffari (Mazandaran University of Medical Sciences, 2022)
Chronic Urticaria (CU) is a skin disorder characterized by wheal and flare with a duration of more than 6 weeks affecting 1%-2% of the population (more common in women). Thirty to 35% of cases of CU have angioedema [1]. The etiology of chronic spontaneous urticarial is not usually clear, 40%-50% are idiopathic and 30%-40% are autoimmune [2, 3]. Quality of life in CU is usually disturbed which has a direct relation with severity [4].